Towards a geopolitics of carbon capture & storage (CCS) in Asia: Transregional links and implications for Germany and Europe - Dawud Ansari; Rosa Melissa Gehrung; Jacopo Maria Pepe (Stiftung Wissenschaft und Politik (SWP), 2024)
The competition for carbon capture, storage, and utilisation is intensifying. Historically dominated by North America, the lead in this technology is now being seized by key players across Asia - reaching from Saudi Arabia to Japan. Unlike traditional energy (transition) geopolitics, this new arena prioritises technology, geology, and industrial leadership over raw materials. For Germany and Europe, the developments imply a need for more pragmatism in climate diplomacy and policy instruments. Moreover, to keep pace with competitors, policymakers should adopt a proactive approach to CCS vis-à-vis technology and industry.
Keywords: 320; Carbon Capture and Storage; CCS; Carbon Capture; Utilisation and Storage; CCUS; Direct Air Carbon Capture and Storage; DACCS; blue hydrogen; energy transition; Paris Agreement; Gulf states; Australia; Japan; Korea; Indonesia; Malaysia; China; USA; Canada; technopolitics; geopolitics; industrial leadership; technological competition